Usando assertivas de correspondência para especificação e geração de visões XML para aplicações Web - Lemos, Fernando Cordeiro de (2007)
Web applications that have large number of pages, whose contents are dynamically extracted from one or more databases, and that requires data intensive access and update, are known as "data-intensive Web applications" (DIWA applications) [7]. In this work, the requirements for the content of each page of the application are specified by an XML view, which is called Navigation View (NV). We believe that the data of NVs are stored in a relational or XML database. In this work, we propose an approach to specify and generate NVs for Web applications whose content is extracted from one or more data sources. In the proposed approach, a NV is specified conceptually with the help of a set of Correspondence Assertions [44], so that the definition of NV can be generated automatically based on assertions of view.